On Some Iterative Methods with Memory and High Efficiency Index for Solving Nonlinear Equations - Tahereh Eftekhari (International Journal of Differential Equations)
Based on iterative methods without memory of eighth-order convergence proposed by Thukral (2012), some iterative methods with memory and high efficiency index are presented. We show that the order of convergence is increased without any additional function evaluations. Numerical comparisons are made to show the performance of the presented methods.